JUAL BELI DI BIDANG AGRIBISNIS DALAM PERSPEKTIF ISLAM - Haris Susanto; H. Mashadi; Meli Sasmi; Jamalludin; Andi Alatas; Chezy WM Vermila; Nariman Hadi; Eldipama Kesambamula (Fakultas Pertania Universitas Muara Bungo, 2023)
The purpose of this community service is to find out how to do muammalah correctly, which is taught by Islam and add to our insight and knowledge about muammalah in Islam. Community service for the Agribusiness Study Program, Faculty of Agriculture, Islamic University of Kuantan Singingi (UNIKS), provides results of community service activities that have been carried out for lecturers, staff, and students within the UNIKS environment running smoothly. Buying and selling is the exchange of goods. This has been practiced by primitive people when money has not been used as a medium of exchange for goods, namely the barter system which in Fiqh terminology is called Ba'i Al-Muqayyadah. religion, one of which is buying and selling in which there is an unclear element (gharar), something speculative, or vague. Transactions of this kind are unlawful to do, because they can harm one of the contracted parties, both the seller and the buyer. As devout Muslims there is nothing wrong for us to muammalah, but muammalah in a way that has been recommended in Islam which has taught by Rasulullah and his previous companions.Keywords: Buying and Selling, Agribusiness, Perspective, Islam